2015
DOI: 10.17479/jacs.2015.5.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Pressure Ulcer in Severe Trauma Patients

Abstract: This study identifies risks for pressure ulcer in patients admitted to surgical intensive care units because of severe traumatic injuries with injury severity scores of 15 or higher. Methods: Data was collected from records of patients admitted from January 1, 2011, to December 31, 2013. The analysis addressed general characteristics, trauma-related characteristics, and treatment-related characteristics of pressure ulcers. Descriptive statistics include the raw numbers, percentages, and the standard deviations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 18 publications
3
6
5
Order By: Relevance
“…Patients with an ISS of 25 points or higher had a lower risk of PI development than patients with an ISS of 15 points or lower. In a previous study (Jung et al, 2015) on patients with severe trauma, the ISS score of the PI group was higher than that of the non-PI group, which is different from the results of this study. A Brazilian study evaluated the ISS and identified significant differences in the ISS values between groups with high and medium/low nursing activity scores; patients who required a high nursing workload presented with a greater severity of trauma (de Souza Nogueira et al, 2014); therefore, it is possible that nurses provide more aggressive nursing care to severe patients, which may influence the incidence of PIs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Patients with an ISS of 25 points or higher had a lower risk of PI development than patients with an ISS of 15 points or lower. In a previous study (Jung et al, 2015) on patients with severe trauma, the ISS score of the PI group was higher than that of the non-PI group, which is different from the results of this study. A Brazilian study evaluated the ISS and identified significant differences in the ISS values between groups with high and medium/low nursing activity scores; patients who required a high nursing workload presented with a greater severity of trauma (de Souza Nogueira et al, 2014); therefore, it is possible that nurses provide more aggressive nursing care to severe patients, which may influence the incidence of PIs.…”
Section: Discussioncontrasting
confidence: 99%
“…The risk factors of PIs in patients with TBI admitted to the ICU were the use of mechanical ventilation, period of enteral feeding (more than 7 days), period of fever (more than 7 days), vasopressor infusion, lower BSS, and ISS (25 points or more). In this study, the use of mechanical ventilation resulted in 11.54-fold greater risk of PI development, which was higher than that reported in patients admitted to the ICU (6.08-fold) (González-Méndez et al, 2018) or with severe trauma (4.54-fold) (Jung et al, 2015). The lives of patients with severe TBI are sustained by specialized treatments (Ngubane, 2011), including mechanical ventilation, due to impaired consciousness and motor deficits (Dhandapani et al, 2014).…”
Section: Discussioncontrasting
confidence: 62%
“…Of the 315 patients with severe trauma, 42 patients developed pressure ulcers, corresponding to 13.3% of patients. The reported incidence of pressure ulcers in South Korea is from 9% to 17% [12,24], and internationally it has been reported as 28.3% [13]. These results are affected by differences in patients' general characteristics, trauma type, and treatment characteristics as well as by social and cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma-related characteristics were collected through the information entered into the Korean Trauma Data Base. Based on the items collected from a previous study, this information was organized into five items: mechanism of injury, trauma type, parts of damage, ISS, and admission route [12].…”
Section: Characteristics Related To Traumamentioning
confidence: 99%
See 1 more Smart Citation